(untitled) (IMC Journal of Medical Science, 2017)
Background and objectives: Gastrointestinal (GI) disorders are contributor of increased morbidity and poor quality of life in individuals with diabetes mellitus (DM). Racial, nutritional and life style may influence GI disorders to a large extent. Thus, the burden of GI disorders and its determinants warrant investigation in individual population. Therefore, the present study was undertaken to explore the types of GI symptoms in Bangladeshi population with DM for more than 10 years of duration. Methodology: This observational study was conducted on patients with DM for more than 10 years of duration at the outpatient department of BIRDEM general hospital from July 2009 to June 2010. A total of 301 DM patients responded to self-reporting questionnaire (Bengali adaptation of Rome III diagnostic questionnaire). Then 91 participants were further studied for glycemic status, liver function, kidney function and basic defects of diabetes through homeostasis model assessment. Results: The median age of 301 study population was 55 years (range 25 to 84 years) and the male female ratio was 1: 0.74. Out of 301 DM cases, 273 (90.7%) had GI symptoms. Significantly (p<0.05) higher number of males (93.6%) had GI symptoms compared to females (86.7%). Among the clinical conditions, unspecified functional bowel disorder (UFBD) was present in 88.3% cases, followed by cyclic vomiting syndrome (38.1%) and functional fecal incontinence (20.9%). Single GI symptom was present in 123 (45.1%) cases while 32.6%, 12.5% and 9.9% had two, three and more than three GI symptoms respectively. No significant difference was found in any biochemical parameter between cases with and without GI symptoms. Multiple logistic regression analysis revealed sex and residence as poor predictors of UFBD while other variables did not show any significant relation/risk to UFBD. Conclusion: A large proportion of patients with long duration of DM had GI symptoms. A comprehensive management of diabetes requires attention to GI disorders. IMC J Med Sci 2017; 11(2): 56-60